The Type II Secretory System Mediates Phage Infection in Vibrio cholerae - Sun, Huihui; Liu, Ming; Fan, Fenxia; Li, Zhe; Fan, Yufeng; Zhang, Jingyun; Huang, Yuanming; Li, Zhenpeng; Li, Jie; Xu, Jialiang; Kan, Biao (Frontiers in Cellular and Infection Microbiology, 2021)
Attachment and specific binding to the receptor on the host cell surface is the first step in the process of bacteriophage infection. The lytic phage VP2 is used in phage subtyping of the Vibrio cholerae biotype El Tor of the O1 serogroup; however, its infection mechanism is poorly understood. In this study, we aimed to identify its receptor on V. cholerae. The outer membrane protein EpsD in the type II secretory system (T2SS) was found to be related to VP2-specific adsorption to V. cholerae, and the T2SS inner membrane protein EpsM had a role in successful VP2 infection, although it was not related to adsorption of VP2. The tail fiber protein gp20 of VP2 directly interacts with EpsD. Therefore, we found that in V. cholerae, in addition to the roles of the T2SS as the transport apparatus of cholera toxin secretion and filamentous phage release, the T2SS is also used as the receptor for phage infection and probably as the channel for phage DNA injection. Our study expands the understanding of the roles of the T2SS in bacteria.